BUSINESS EDUCATION: TRAINING IN THE USE OF BLOCKCHAIN TECHNOLOGY FOR BUSINESS DEVELOPMENT - Mikhailovna Milovanova, Marina; Sergeevna Markova, Tatyana; Mushrub, Vladimir; Evgenievna Ordynskaya, Marina; Valerievna Plaksa , Julia (Revista Inclusiones, 2020)
The rapid development of information technologies, the hybridity of modern cyber threats and vulnerabilities, and the failure of traditional cryptosystems to resist cyber-attacks require the use of new approaches to form a secure business process contour. One of these approaches is the formation of decentralized systems based on blockchain technology, which is rapidly spreading in various sectors of society. The basic principle that underlies it is the peer-to-peer privileges of all users of such systems based on cryptographic digital signature protocols and hashing. These, as well as other advantages and properties of blockchain technologies, ensure their spread and the rapid spread of decentralized systems using cryptocurrencies. Based on an expert survey, the main provisions of the "Blockchain: Fundamentals and Application Examples" business education course have been developed, the competencies and learning outcomes for this course have been determined, and the sample business program "Blockchain: Fundamentals and Application Examples" has been presented.